Website Creation as Means of Digitizing MSME Products for School Uniforms at Agung's Collection - Eko Wahyudi; Anggraini Puspita Sari; Firza Prima Aditiawan (Nusantara Science and Technology Proceedings, 2022)
The development of digital technology provides opportunities for micro, small, and medium enterprises (MSMEs) to utilize online media in marketing strategies that were initially only conventional in the hope of increasing the income of MSME actors. Agung's Collection is an MSME actor who was selected as a partner for community service activities financed by the East Java "Veterans" National Development University. The partner business was built in the 90s and was led directly by the business owner, namely: Mr. Mustik. Agung's Collection is a special partner in producing school uniforms located in Sraturejo Village, Baureno sub- districts, Bojonegoro districts, Indonesia. The stages of community service activities that have been carried out are conducting partner location surveys, outreach to partners, problem analysis, product digitization implementation, and intellectual property rights (IPR) management. The training and assistance phase of the results of product digitization will be carried out after reporting accountability to the Research and Community Service Institute (LPPM), Universitas Pembangunan Nasional “Veteran Jawa Timur, Surabaya-Indonesia. This community service activity is in the form of digitizing partner products to expand marketing reach, increase sales results, maintain product quality, and increase productivity so that it has an impact on increasing partner income significantly which is expected to improve the welfare of partner employees. The results of digitizing partner products carried out by the proposing team consist of a website, tag, and logo. Design of tag, logo, and website based on the agreement between the proposer team and partners. Tag and logo are designed based on the characteristics or uniqueness of partner products so that they are different from other school uniform manufacturers. On the website, the results of Agung's Collection logo design are already listed. The website contains a home, about us, galleries, products, and contacts.